FR1.1: The process to "Gender Expert" in gender and agriculture: Learning from the GREAT model - Garner, Elisabeth L.P. (Center for International Forestry Research, 2022)
The goals of gender equity and the resulting increased attention to and funding for gender mainstreaming have increased the number of gender experts. This is true throughout policy and development organizations, as well as agricultural research institutes as donors and program requirements demand social equity goals. While previous discussions have focused on the experience of gender experts within institutions, there is limited discussion on how gender experts acquire their expertise and whether there are variations among this expertise. The Gender-responsive Researchers Equipped for Agricultural Transformation (GREAT) provides a unique opportunity to consider the "gender expert" in agriculture and rural development. Using the GREAT model as the context, this paper examines the potential of gender trainings to support the development of gender expertise, and the limitations of that process. The result is an examination of the term "gender expert" and its use given the diversity of knowledge and experience that can fall under its understanding.